Compressibility characteristics of collapsible gypseous soil: A review - Hassan Al-Riahi S.M.; Pauzi N.I.M.; Fattah M.Y. (Institute of Physics, 2024)
Gypseous soil is located in dry and semi-arid areas in unsaturated conditions and this type of soil becomes a serious issue for engineering and geotechnical when it becomes wet. the properties and structure of this soil change, when exposed to soaking and leaching, because gypsum is dissolved in water causing a rupture in the bonds that hold soil particles together and a reduction in the suction power that holds them together. Large settlements and potential collapse will happen which cause problems for the constructions built on it. This paper gives an overview of some of the properties of gypseous soils and previous research on the behavior of this soil. It was found that the collapse potential of gypseous soil increases with increasing the gypsum content and void ratio, and collapse potential decreases when the initial water content and dry density increase. Published under licence by IOP Publishing Ltd.